Preparation of Fullerene (C60) Nanowhisker-ZnO Nanocomposites by Heat Treatment and Photocatalytic Degradation of Methylene Blue - Hwi Cho, Bum; Bong Lee, Kyu; Miyazawa, Kun'ichi; Bae Ko, Weon (Asian Journal of Chemistry, 2013)
The fullerene (C60) nanowhisker (FNW) nanoparticles were synthesized by the liquid-liquid interfacial precipitation method using good solvent solutions such as pyridine, benzene and toluene saturated with C60 and isopropyl alcohol as a polar solvent. The zinc oxide nanoparticles were synthesized sonochemically by applying ultrasonic irradiation to a mixed aqueous-alcoholic solution of zinc nitrate with sodium hydroxide at room temperature. The heated FNW-ZnO nanocomposites were synthesized in an electric furnace at 700 ºC for 2 h. The heated FNW-ZnO nanocomposites were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. In addition, by using UV-visible spectrophotometer, the heated FNW-ZnO nanocomposites were determinable as a catalyst in the photocatalytic degradation of methylene blue. The photocatalytic effect of the heated FNW-ZnO nanocomposites were confirmed as being compared with unheated FNW-ZnO nanocomposites in methylene blue under ultraviolet light at 254 nm.